Antioxidant ability of alcoholic infusions from vegetable raw materials for the technology of alcoholic beverages - Kuzmin, Oleg; Kucherenko, Volodymyr; Stukalska (Ivanova), Nataliia; Kuts, Anatoly; Oliynyk, Svitlana; Rakhmetov, Jamal (My University, 2020)
The work is devoted to the development of scientific foundations of the antioxidant activity of aqueous-alcoholic infusions from plant raw materials and the identification of the most promising plants as sources of natural antioxidants. The creation of alcoholic tinctures with an antioxidant effect makes it possible to bring to the market new products that favorably distinguish the range of manufacturers from the range of competitors, creating a positive image of the company. Expansion of the range of alcoholic beverages with the use of alcoholic beverages from plant raw materials to enhance the antioxidant effect has been substantiated.
Keywords: alcohol; antioxidant; redox; beverage; infusion; алкоголь; напої; антиоксидант; окислювально-відновний; настій; кафедра технології ресторанної і аюрведичної продукції; кафедра біотехнології продуктів бродіння і виноробства